1991
DOI: 10.1016/0270-9139(91)90267-y
|View full text |Cite
|
Sign up to set email alerts
|

Diet and cimetidine induce comparable changes in theophylline metabolism in normal subjects

Abstract: This study compared the effects of diet and cimetidine on theophylline metabolism and examined interactions between these effects. Twelve men received a high-protein diet for 15 days and at another time a high-carbohydrate diet also for 15 days. Cimetidine, 800 mg daily at bedtime, was administered on days 10 through 15 of each dietary period. Theophylline metabolism was studied after the administration of a single intravenous 3 mg/kg dose on days 8 and 15 of each dietary period. Changing from a high-protein t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…To evaluate circadian differences, the area under the theophylline serum concentration versus time curve during each dosing interval, AUC (0-12) and AUC (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) , was calculated. In addition, oral clearance was evaluated as CLo (0-12) and CLo (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . Differences in the pharmacokinetics of theophylline between the day (0-12) and night (12-24) dosing intervals were described descriptively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate circadian differences, the area under the theophylline serum concentration versus time curve during each dosing interval, AUC (0-12) and AUC (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) , was calculated. In addition, oral clearance was evaluated as CLo (0-12) and CLo (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . Differences in the pharmacokinetics of theophylline between the day (0-12) and night (12-24) dosing intervals were described descriptively.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary changes may actually affect theophylline to the same extent as standard doses of cimetidine. 16 Theophylline adverse effects were most common following initiation of treatment. Most of the subjects in this study reported nervousness, tremor, palpitations, mental disturbances, and nausea in the first 2 to 3 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP3A4 enzyme induction has been observed with concomitant use of St. John's wort ( Hypericum perforatum ) which can result in increased metabolism of CYP3A4 substrates [10]. Similarly, food substances found in charbroiled beef, cruciferous vegetables (cabbage and sprouts), high protein diet [43] and constituents of tobacco [44] can induce CYP1A2. On the other hand, inhibition of CYP enzymes may also occur with concurrent use of grapefruit juice containing narigenin [45] that inhibits CYP3A4 which is responsible for metabolism of a large number of psychotropics.…”
Section: Impact Of Environmental Variablesmentioning
confidence: 99%
“…Dietary factors, herbal medication, chemicals and even pollutants are exogenous agents that may alter the activity of drug-metabolizing enzymes, particularly CYP1A2 and CYP3A4 [41]. Similarly, food substances found in charbroiled beef, cruciferous vegetables (cabbage and sprouts), high protein diet [43] and constituents of tobacco [44] can induce CYP1A2. Studies have shown that Asians and Africans exposed to Western diets and environment do not exhibit the same sensitivity to psychotropics as those living in their native countries [42].…”
Section: Impact Of Environmental Variablesmentioning
confidence: 99%